Soluble ACE2 and angiotensin II levels are modulated in hypertensive COVID-19 patients treated with different antihypertension drugs. (31st December 2022) - A. Elrayess, Mohamed; T. Zedan, Hadeel; A. Alattar, Rand; Abusriwil, Hatem; Al-Ruweidi, Mahmoud Khatib A. A.; Almuraikhy, Shamma; Parengal, Jabeed; Alhariri, Bassem; Yassine, Hadi M.; A. Hssain, Ali; Nair, Arun; Al Samawi, Musaed; et al.
Abstract: Purpose: This study examines the effect of antihypertensive drugs on ACE2 and Angiotensin II levels in hypertensive COVID-19 patients. Introduction: Hypertension is a common comorbidity among severe COVID-19 patients. ACE2 expression can be modulated by antihypertensive drugs such as ACEis and ARBs, which may affect COVID-19's prognosis. BB and CCB reduce mortality, according to some evidence. Their effect on circulating levels of ACE2 and angiotensin II, as well as the severity of COVID-19, is less well studied. Materials and methods: The clinical data were collected from 200 patients in four different antihypertensive medication classes (ACEi, ARB, BB, and CCB). Angiotensin II and ACE2 levels were determined using standard ELISA kits. ACE2, angiotensin II, and other clinical indices were evaluated by linear regression models. Results: Patients on ACEi ( n = 57), ARB ( n = 68), BB ( n = 15), or CCB ( n = 30) in this study had mild ( n = 76), moderate ( n = 76), or severe ( n = 52) COVID-19. ACE2 levels were higher in COVID-19 patients with severe disease ( p = 0.04) than mild ( p = 0.07) and moderate ( p = 0.007). The length of hospital stay is correlated with ACE2 levels ( r = 0.3, p = 0.003). Angiotensin II levels decreased with severity ( p = 0.04). Higher ACE2 levels are associated with higher CRP and D-dimer levels. Elevated Angiotensin II was associated with low levels of CRP, D-dimer, and troponin. ACE2 levels increase with disease severity in patients taking an ARB ( p = 0.01), patients taking ACEi, the degree of disease severity was associated with a decrease in angiotensin II. BB patients had the lowest disease severity. Conclusion: We found different levels of soluble ACE2, and angiotensin II are observed among COVID-19 patients taking different antihypertensive medications and exhibiting varying levels of disease severity. COVID-19 severity increases with elevated ACE2 levels and lower angiotensin II levels indicating that BB treatment reduces severity regardless of levels of ACE2 and angiotensin II.